Bsm1 vitamin D receptor polymorphism and calcium homeostasis following bariatric surgery - Alexandrou, A; Armeni, E.; Kaparos, G.; Rizos, D.; Tsoka, E.; Deligeoroglou, E.; Creatsa, M.; Augoulea, A.; Diamantis, T; Lambrinoudaki, I. (Journal of Investigative Surgery, 2015)
Copyright © 2015 Informa Healthcare USA, Inc. Purpose/Aim: To evaluate the association between the Bsm1 vitamin D receptor polymorphism and the calcium-vitamin D-parathormone axis following bariatric surgery. Materials and Methods: This cross-sectional study included 86 morbidly obese patients, who underwent either gastric bypass or sleeve gastrectomy, with a mean follow-up of four years. Calcium metabolism indices and bone turnover markers were assessed according to the presence of secondary hyperparathyroidism and the Bsm1 vitamin D receptor genotypes. Results: Secondary hyperparathyroidism (42.2% of sample) was associated with lower levels of 25hydroxyvitamin D and elevated markers of bone turnover. In subjects without secondary hyperparathyroidism, presence of the unfavorable B allele resulted in higher levels of parathormone (Bb and BB vs. bb genotype: 50.3 ± 8.2 pg/dl vs. 44.4 ± 10.7 pg/dl, p = .011, adjusted for weight loss, baseline body mass index, 25hydroxyvitamin D, surgical procedure, and duration after surgery). In the whole sample, patients bearing the unfavorable B allele exhibited lower weight loss, a parameter that was negatively associated with markers of bone resorption. Conclusions: Secondary hyperparathyroidism is highly prevalent after bariatric surgery. Bsm1 vitamin D receptor polymorphism may have an effect in early stages of calcium metabolism imbalance, while no association is detected in patients who have already developed secondary hyperparathyroidism. Moreover, vitamin D receptor polymorphism is associated with post-surgery weight loss, a process related to bone turnover.
Keywords: Bariatric Surgery; Bsm1 VDR polymorphism; Calcium metabolism; Parathormone; Roux-en-Y Gastric bypass; Sleeve gastrectomy